Partisipasi Masyarakat Dalam Program Desa Berdaya Di Desa Kedungpring Kecamatan Balongpanggang Kabupaten Gresik - Velinda Ayu Sasmita; Arif Darmawan; Muhammad Roisul Basyar (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
Community participation is very necessary for the success of a program in developing and improving the quality of community life. Community participation in the empowered village program is proof of awareness, concern and responsibility for developing village potential in improving the quality of life of the community. The active involvement of the community has great significance in the success of a program to achieve successful village development and the government also collaborates as a facilitator to drive development at the village level. This type of research uses descriptive qualitative research which aims to determine the form of community participation in the Empowered Village Program in the form of the construction of the Pring Jenggala Buffet and Café in Kedungpring Village. This descriptive qualitative research was carried out with the aim of finding out how the community participated in the Empowered Village Program, namely the construction of the Pring Jenggala Buffet and Cafe in Kedungpring Village. This research collects data through literature research as well as written words. The results of research and discussions show that the people of Kedungpring Village are well involved in the empowered village program. The community is always involved in the form of thought, energy, expertise and participation in the form of goods in the introduction, planning, implementation, monitoring and evaluation stages of empowered village program activities. However, the form of participation that is less involved is monetary participation. Because the community has not been given the obligation to make contributions to the empowered village program.